Comparación de técnicas de curación de heridas en adultos mayores con úlceras por presión - Pandi Córdova, Gabriela Elizabeth (2025)
Pressure ulcers are nowadays a health problem, especially in people considered to be at risk, since they directly affect the quality of life of the patient and his or her environment. Therefore, it was decided to carry out a systematic review in order to group together the latest recommendations on pressure ulcer prevention in order to help in deciding the correct way to act with our patients. The objective is to compare the efficacy of different wound healing techniques in the treatment of pressure ulcers in older adults. The present study is a descriptive type of research, it included the review of scientific papers and articles. The selection was made through databases such as Google Scholar, Dialnet and Scielo. The review covered a period of analysis between the years 2019 and 2023 and followed the PRISMA 2020 guidelines to ensure clear and accurate publication. From the review, figures on the cost of ulcer treatment, both personal and economic, were obtained as a result and has made it clear that investing in good prevention is very important and is more beneficial for all. Subsequently, the latest advances in prevention have been grouped together and false beliefs have been disproved, and the information can be used to make a comparison of techniques for healing pressure ulcers in older adults.